2018
DOI: 10.5114/cipp.2018.75750
|View full text |Cite
|
Sign up to set email alerts
|

Performing developmental tasks in emerging adults with childhood parentification – insights from literature

Abstract: Parentification is the process of role reversal between the child and the parent, whereby the child provides support and acts as the caregiver for the parent, instead of being supported and taken care of. The phenomenon of parentification may afflict families at diverse stages of development, including those before as well as after the phase of empty nest. Parentification may then pertain a threat to the development of a young person by impeding or preventing him or her from fulfilling developmental tasks. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Next, a set of hierarchical multiple regressions were run on attachment-related anxiety and avoidance in order to analyze the predictive ability of each parent’s positive strategies towards the other during the divorce process, each parent’s negative emotional state associated with the process of divorce, and post-divorce interparental conflict. Because cross-gender parent–child dyads in family parentification processes might play a differential role in emerging adult children’s romantic relationships [ 47 ], initially, interactions with child’s gender were also tested. Given that these resulted non-significant, interactions with child’s gender were not included in our regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Next, a set of hierarchical multiple regressions were run on attachment-related anxiety and avoidance in order to analyze the predictive ability of each parent’s positive strategies towards the other during the divorce process, each parent’s negative emotional state associated with the process of divorce, and post-divorce interparental conflict. Because cross-gender parent–child dyads in family parentification processes might play a differential role in emerging adult children’s romantic relationships [ 47 ], initially, interactions with child’s gender were also tested. Given that these resulted non-significant, interactions with child’s gender were not included in our regression models.…”
Section: Methodsmentioning
confidence: 99%
“…The relations among types of parentification, school achievement, and quality of life in early adolescence: an exploratory study. Frontiers in Psychology, 12, artykuł 635171. https:// doi.org/10.3389/fpsyg.2021.635171 Borchet, j., lewandowska-Walter, a., rostowska, t. (2018). performing developmental tasks in emerging adults with childhood parentification -insights from literature.…”
Section: Podsumowaniementioning
confidence: 99%
“…The study group consisted mainly of students who are going through the period of emerging and young adulthood. It is the time when young people postpone their decisions to form a relatively stable relationship, start a family, give birth to their first and next child, and leave their family home (Borchet, Lewandowska-Walter, & Rostowska, 2018;Brzezińska, Kaczan, Piotrowski, & Rękosiewicz, 2011), and "this population of emerging adults has shown that they gradually achieve important developmental markers for adulthood (…)" (Barry, Madsen, Nelson, Carroll, & Badger, 2009, p. 220). Moreover, our sample was predominated by women, and -as prior studies demonstrated -gender differences do exist in the domain of love styles (Mandal & Latusek, 2018), with women perceiving love as Mania or Pragma (Hendrick & Hendrick, 1995).…”
Section: Substantive Analysesmentioning
confidence: 99%